PEMANTAUAN KADAR LOGAM BERAT DALAM AIR LAUT DAN SEDIMEN DI PERAIRAN PULAU BACAN, MALUKU UTARA - Marasabessy, M Djen; Edward, Edward; Valentin, Febriana Lisa (Makara Journal of Science, 2010)
Monitoring on Heavy Metals Content in Sea Water and Sediment in the Waters of Bacan Island, North of Maluku. Measurement on heavy metals content in seawater and sediment in the waters of Bacan Islands, North of Maluku were carried out in September 2005. That heavy metals are Pb, Cd, Cu, Zn, and Ni. Seawater and sediment sample collected from 10 station by purposive sampling, in line with the goal of the research. The results showed that the heavy metals content in seawater still in line with the threshold value (NAB) stated by The Office of State Ministry for Life Environment (KMNLH) but in sediment heavy metals content is high relative, especially Cu and Ni has passed the threshold value for sediment. Beside heavy metal content also measured physical and chemical parameters such as temperature, salinity, total suspended solid, light transmission, dissolved oxygen, acidity, phosphate and nitrate. The result also indicated that parameters still in line with the threshold value stated by KMNLH for marine organism. Based on heavy metals content, the value of seawater quality status included into class A (fine) with score 0. Heavy metal content in sediment is higher than seawater, this condition indicated there are heavy metals accumulation in sediment.